(untitled) (Al-Academy, 2021)
The features of the actor’s performance in the ritual theater are of great importance and chief in theatrical work since the first emergence of the theater, as the features of the performance were embodied in all Iraqi theatrical performances, but they took personal privacy in some ritual performances because of their differences and similarities between the ritual theatrical performance and the ritual show Al-Khalis, who wanted the researcher to know the similarities and differences in the features of the ritual performance and in the theatrical performance, despite the many transformations that occurred in the theater and affected the features of the performance, but it remained an important and attractive link between the recipient, the performer and the actor, the representative performance studies tried to establish a theoretical framework The effects of the weather according to the intertwining cultural perspective and at the same time the broader theatrical response in theatrical productions, as the similarity between ritual and theater does not lie in the formal aspect but in their effect on the recipient, and despite its specificity, the researcher therefore found the necessity to clarify the ritual in relation to the theater and how it can be crystallized in The actor’s performance system, although the ritual does not accept development for religious reasons and remains closed, but it can take the character of a vista partly because of the interest of people in it from I hope the participating group. This is the state of watching from outside, which appears in a number of vulgar performances in which the group participates, such as the Mevlevi celebrations and the rituals of striking the shish in the Rifa’i presence, which is received by spectators from outside the sons of the Tariqa